Potential of indigenous bacteria from West Sumatra (Indonesia) as plant growth-promoting rhizobacteria and biological soil conditioners in vitro - YULENSRI YULENSRI; BENNY WARMAN; NOVERI NOVERI; FRI MAULINA (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Yulensri, Warman B, Noveri, Maulina F. 2025. Potential of indigenous bacteria from West Sumatra (Indonesia) as plant growth-promoting rhizobacteria and biological soil conditioners in vitro. Biodiversitas 26: 3378-3386. Farmers depend on chemical fertilizers to increase rice production in the lowlands. As a result, rice fields have become critical due to physical, chemical, and biological degradation caused by the continuous use of chemical fertilizers and environmental pollution from residues. The use of potential indigenous bacteria could solve the problem. Therefore, this study aimed to isolate the indigenous bacteria from the banana stump in West Sumatra and the rhizosphere of the maize plant. The isolated bacteria were identified for their potential as plant growth-promoting rhizobacteria and biological soil conditioners. The experiment was conducted from March to May 2024 at the Plant Protection Laboratory of Politeknik Pertanian Negeri Payakumbuh and the Biotechnology Laboratory of the Institut Pertanian Bogor, Indonesia. The variables observed were the potential of bacteria as N fixers, P solubilizing, secretion of protease, kinase, cellulase enzymes, and exopolysaccharide (EPS). The results of the molecular analysis showed that potential isolates were Azotobacter beijerinckii Lipman, 1904 and Alcaligenes faecalis C. Both bacteria showed potential as PGPR and biological soil conditioners, which positively fixed nitrogen, can solubilize phosphate, produce auxins, and secrete chitinase, cellulase, protease enzymes, and EPS.